Factors Affecting Forest Product Exports - Saraswati, Ria Indah; Harianto, Harianto; Rifin, Amzul (Jurnal Manajemen & Agribisnis, 2023)
Large-scale companies carry out forestry industry export activities. PT SLJ Global Tbk is one of the actors in this activity. The research’s objectives are to analyze the factors that affect the company's plywood exports and to identify the managerial policies of the company's plywood exports. This research uses secondary data in the form of monthly time series data form January 2014 to December 2020. The Error Correction Model (ECM) is used to analyze the factors that affect the company’s plywood export volume. The factors that have a positive and significant effect in the long-term model are the production volume and the previous period's production volume. The factors that have a positive and significant effect on the short-term model are production volume, export prices, international prices, and production volumes for the previous period. The managerial implications are increasing productivity, maintaining production stability, increasing plywood quality, and increasing export marketing. Suggestions for company are to maintain the stability of raw materials, innovate products, increase investment, require new markets, and analyze and evaluate marketing and its correlation with the company's production aspects. Keywords: ECM, export, forestry, managerial, plywood